Molecular homogeneity of heat-stable enterotoxins produced by bovine enterotoxigenic Escherichia coli. - Saeed, A M (1984)
Heat-stable enterotoxins (STs) from four strains of bovine enterotoxigenic Escherichia coli representing four serogroups were purified to homogeneity by utilizing previously published purification schemata. Biochemical characterization of the purified STs showed that they met the basic criteria for the heat-stable enterotoxins of E. coli. Amino acid analysis of the purified STs revealed that they were peptides of identical amino acid composition. This composition consisted of 18 residues of 10 different amino acids, 6 of which were cysteine. The amino acid composition of the four ST peptides was identical to that reported for the STs of human and porcine E. coli. In addition, complete sequence analysis of two of the ST peptides and partial sequencing of several others revealed strong homology to the sequences of STs from human and porcine E. coli and to the sequence predicted from the last 18 codons of the transposon Tn1681. There was also substantial homology to the sequence predicted from the ST-coding genetic element of human E. coli, which may indicate the existence of identical bioactive configuration among ST peptides of E. coli strains of various host origins. These data support the hypothesis that STs produced by human, bovine, and porcine E. coli are coded by a closely related genetic element which may have originated from a single, widely disseminated transposon.